INTEGRATING GENERATIVE AI IN STEM EDUCATION: A PATHWAY TO INCLUSIVE AND ENHANCED LEARNING (Education in the 21st Century, 2024)
This article explores the integration of ChatGPT into STEM education as a means to address educational disparities and enhance learning experiences. Focused on making STEM education more inclusive and accessible, the research delves into ChatGPT's potential to democratize education by overcoming geographical and language barriers, thus providing quality educational resources to underprivileged communities. The study underscores ChatGPT's capabilities in facilitating personalized and interactive learning experiences, supporting complex subject comprehension, and aiding in practical problem-solving and laboratory work. The findings suggest that ChatGPT can significantly enhance the quality and effectiveness of STEM education, making it more engaging and tailored to diverse student needs. The article concludes with a call to action for policymakers, educators, and technology developers to invest in infrastructure and training, ensuring ChatGPT's benefits reach all learners globally, thereby contributing to a more equitable and enlightened future in education.
Keywords: STEM; Artificial Intelligence (AI) in education; GhatGPT; inclusive education; personalized learning; higher education; school; public education; educational equity; educational technologies